ENDOVASCULAR TREATMENT FOR TOTALLY IMPLANTABLE CENTRAL VENOUS ACCESS DEVICE-RELATED SUPERIOR VENA CAVA SYNDROME — CASE REPORT - Fróis Borges, Miguel (2017)
Introduction: Benign superior vena cava syndrome (SVCs) is rare and may be related to a totally implantable vascular access device (TIVAD). In the past 20 years, percutaneous endovascular placement of a stent has been rising as a viable option for SVCs treatment. Case Report: We report the case of a 42-year-old woman with the diagnosis of classical Hodgkin lymphoma who presented a SVCs one year after placement of a TIVAD. After failure of conservative treatment, we placed an auto-expansible stent through the TIVAD with good radiologic and clinical result. Conclusion: Endovascular treatment for TIVAD-related SVCs is safe and may be considered a first line approach.